Analisis Beban Kerja Petugas Rekam Medis RSUD DR. R. Soedarsono Pasuruan - Tatsbita Sabrina; Lilik Afifah; Fita Rusdian Ikawati (Universitas Muhammadiyah Manado, 2024)
Medical records are a hospital service that stores patient identity data and plays a role in making medical decisions. Analysis of the workload of medical records officers is needed to ensure efficiency and effectiveness in implementation. This study aims to identify and evaluate the workload of medical records officers at RSUD dr. R. Soedarsono Pasuruan using the Health Workload Analysis (ABK-KES) method. This study is quantitative descriptive in nature with data collection methods in the form of observation, interviews, questionnaires, and document review. Research findings reveal that there is inequality in the distribution of workload in various medical records units, which can impact the quality of hospital services. Therefore, researchers suggest that the workforce with D3 and D4 qualifications still needs to be increased to support higher quality services and it is necessary to optimize the number of workers and make the workload distribution more balanced. Hospital management is also advised to recruit D3 and D4 staff to be more competent in medical record management and training to increase the effectiveness of services at the hospital. Optimizing the workforce by ABK-KES, medical services are expected to operate more effectively so a strategy for optimizing the number and distribution of the workforce is needed to increase service efficiency.